A REVIEW OF THE TROPICAL DEVELOPMENT AND RESEARCH INSTITUTE'S CONTRIBUTION TO THE COCONUT INDUSTRY - D. ADAIR; J.H. BROADBENT (International Coconut Community, 1986)
The Tropical Development and Research Institute (TDRI) was formed on l April 1983 by the amalgamation of the Tropical Products Institute (TPI) and the Centre for Overseas Pest Research (COPR). The Institute has a long history of providing assistance and advice to developing countries in post‑harvest aspects of food and other agricultural commodities, which include the many products dexived from the coconut. This review covers the Institute's work over the last ten years and illustrates the wide range of interests concerning coconuts. These cover research and development on dehusking and processing projects, economic studies for the establishment of new coconut‑based industries, and technological improvements for the manufacture of charcoal from coconut shell.